A comparative study of different tissue materials for bioprosthetic aortic valves using experimental assays and finite element analysis. (June 2022) - Rassoli, Aisa; Fatouraee, Nasser; Guidoin, Robert; Zhang, Ze; Ravaghi, Saba
Highlights: The long term durability of bioprosthetic heart valves is largely determined by the leaflet tissues. Selecting the pericardium based on its adequate mechanical property will increase the lifetime of these prostheses. The visco-hyperelastic properties of bovine, donkey, equine and porcine pericardium and finite element modeling of these tissues by using the exact mechanical properties have not been investigated previously. Decreasing mechanical stress in the bioprosthetic leaflets should reduce tissue degeneration and increase the long-term durability of the valve. The best pericardium tissue was selected due to the low stress on the leaflets during the systolic and diastolic phases and the large geometric orifice area. Abstract: Background and objective: Extracting the mechanical behaviors of bioprosthetic aortic valve leaflets is necessary for the appropriate design and manufacture of the prosthetic valves. The goal of this study was to opt a proper tissue for the valve leaflets by comparing the mechanical properties of the equine, porcine, and donkey pericardia with those of the bovine pericardium and human aortic valve leaflets. Methods: After tissue fixation in glutaraldehyde, the mechanical behaviors of the pericardial tissues were experimentally evaluated through computational methods. The relaxation tests were performed along the tissue fiber direction. The Mooney-Rivlin model was utilized to describe the hyperelastic behavior of the tissues at the ramp portion. The viscous behaviors at the hold portion were extracted using the Fung quasi-linear viscoelastic (QLV) model. Furthermore, the extracted parameters were used in the modeling of the bovine, equine, porcine, and donkey pericardia through finite element analysis (FEA). Results: Based on the results, relaxation percentages of the equine, donkey, and bovine pericardia were greater than that of the porcine pericardium and similar to the native human aortic valve leaflets. Indeed, the equine and donkey pericardia were found more viscous and less elastic than the porcine pericardium. Compared with the porcine pericardium, the mechanical properties of the equine and donkey pericardia were rather closer to those of the native human leaflets and bovine pericardium. The computational analysis demonstrated that the donkey pericardium is preferable over other types of pericardium due to the low stress on the leaflets during the systolic and diastolic phases and the large geometric orifice area (GOA). Conclusion: The donkey pericardium might be a good candidate valve leaflet material for bioprosthetic aortic valves.